Accountability In Library Management: Issues & Strategies For The 21st Century - Zaiton Osman,; Sharipah Hanon Bidin, (2004)

(untitled)
If libraries are judged on their own merit, in isolation from their parent organisations, the majority in the ASEAN countries can be said to be excellent, even in comparison with libraries in other more developed countries. However it is only when librarians are judged for their role vis a vis their parent organizations that their contribution is seen to be more peripheral rather than integral. For example, most university libraries are not fully integrated into the teaching – learning process which forms the core business of universities. Apart from pedagogical constraints that do not encourage resource-based or informationbased independent learning, the status of librarians has never been acknowledged by the academia to be at par. It is librarians who have always assumed that libraries are critical to national development although not many outside the library community acknowledge the importance of the library’s role.